A Methods engineering study on Joving's Crafts - Dela Cruz, Aurora Patricia (College of Engineering, University of the Philippines Diliman, Quezon City, 1999)
Joving's Craft, a sole proprietorship located in Rosario, Pasig, specializes in the manufacturing of capiz lamshades. It was started in 1982 as a subcontractor of Phil-Italia. Its product line also includes made-to-order capiz products such as Christmas lanterns and souvenir items. It employs a labor intensive program, with all the work done manually (NO MACHINES) by its currently 28 employed crafts people from Samar. The group conducted work measurement, methods study, and time study on Joving's Crafts. The problem areas identified are 1) there is no definite layout, 2) improper handling/storage of materials, and 3) there is no evident systems and procedures nor a flow of forms. The group recommended a change in the facility layout. The group also proposed the installation of bins, containers and tables for proper materials storage and handling. A proposed systems and procedure was also suggested by the group. Proposed forms for the recording of pertinent information was suggested by the group.